SPEECH ACTS IN ONLINE REVIEWS ON UNIVERSITY FACILITIES AND SERVICES: A CORPUS PRAGMATICS STUDY - Aziz, Aisyah Abidatul; Hilyati, Rahma Alya; Meilina, Ivana Cecilia; Pawestri, Sekar; Yuliawati, Susi (Metahumaniora, 2025)
This study aims to analyze online reviews of Universitas Padjadjaran to identify the types of speech acts used, which are evaluative, directive, and analytical, and explore the use of adjectives through a corpus analysis approach. This study aims to understand the public’s view of Universitas Padjadjaran, provide an overview of word frequency, and evaluate the contribution of reviews in building the reputation of educational institutions. This research was conducted using a combined qualitative and quantitative method, as well as the Sketch Engine tool. The data was used to build a corpus containing 215 reviews (7,696 words) for the period 2014-2024 to analyze the frequency of adjective words and classify speech acts based on pragmatic theory. The results showed that adjectives such as “luas,” “nyaman,” and “sejuk” were among the most frequently used, which reflected the reviews’ focus on the emotional and aesthetical aspects of the campus environment. The most dominant speech acts found are evaluative speech acts, which reflect the subjective views of the reviewers regarding their personal experiences. This indicates that the reviews are more emotional than informative, with comments that tend to emphasize subjective impressions rather than objective facts. This research is expected to contribute by showing how online reviews can be a medium that reflects public perceptions of universities, as well as how a corpus analysis approach can be used to understand language patterns in digital reviews. The findings are expected to help educational institutions understand and respond to public opinion to improve institutional reputation